2024
DOI: 10.1001/jamasurg.2023.5394
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Liquid Biopsy for Surgical Patients With Cancer

Kelly M. Mahuron,
Yuman Fong

Abstract: ImportanceLiquid biopsy is an emerging tool with the potential to change oncologic care practices. Optimal clinical applications for its use are currently undefined for surgical patients.ObservationsLiquid biopsy analytes such as circulating tumor cells (CTCs) and circulating tumor DNA (ctDNA) have been the most clinically studied assays and were initially limited to advanced-stage disease. In the metastatic setting, CTCs and ctDNA levels are prognostic. Although their levels correlate with treatment response,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In another study including 1220 oncologists who discussed genomic testing with patients, 50.0% reported often discussing the likely costs of testing and related treatments and 26.3% reported sometimes discussing costs . However, ctDNA testing is already in the clinic and increasingly being used . Most oncologists surveyed showed interest in using ctDNA testing in ACT decision-making for patients with colon cancer, and in a study of patient-reported outcomes from the BESPOKE trial, most patients surveyed said that they valued the ctDNA testing information and would continue ctDNA testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study including 1220 oncologists who discussed genomic testing with patients, 50.0% reported often discussing the likely costs of testing and related treatments and 26.3% reported sometimes discussing costs . However, ctDNA testing is already in the clinic and increasingly being used . Most oncologists surveyed showed interest in using ctDNA testing in ACT decision-making for patients with colon cancer, and in a study of patient-reported outcomes from the BESPOKE trial, most patients surveyed said that they valued the ctDNA testing information and would continue ctDNA testing.…”
Section: Discussionmentioning
confidence: 99%
“… 26 However, ctDNA testing is already in the clinic and increasingly being used. 27 Most oncologists surveyed showed interest in using ctDNA testing in ACT decision-making for patients with colon cancer, 28 and in a study of patient-reported outcomes from the BESPOKE trial, 29 most patients surveyed said that they valued the ctDNA testing information and would continue ctDNA testing.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, a growing interest has emerged in the application of liquid biopsies (LB) as a conceptual strategy to meet above mentioned need. LB represents a noninvasive methodology capable of furnishing crucial diagnostic, therapeutic, and prognostic information across various cancer types 8 11 . Within the realm of liquid biopsy, circulating tumor DNA (ctDNA) is released from apoptotic cancer cells and manifests in diverse proportions within cell-free DNA (cfDNA) 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cfDNA analysis has evolved from a blurred hypothesis to a tangible and reliable clinical tool. Its non-invasive nature, accessibility, and dynamic reflection of tumor evolution offer a stark contrast to traditional tissue biopsies [1][2][3]. Several preclinical and clinical studies have explored the use of cfDNA as an early detector of cancer.…”
mentioning
confidence: 99%